THE ETIOLOGICAL RELATION OF BACILLUS ACTINOIDES TO BRONCHOPNEUMONIA IN CALVES - Smith, Theobald (The Rockefeller University Press, 1921)
A bronchopneumonia of calves in the early months of life is described and its etiology associated definitely with a minute bacillus, Bacillus actinoides. Bacillus pyogenes, Bacillus bovisepticus, and, less frequently, staphylococci and streptococci may appear later in the affected lungs. Subcutaneous injections of cultures of Bacillus actinoides produce large indurations ending in necrosis. Similarly intratracheal injections produce circumscribed necroses of lung tissue. The cultivation of Bacillus actinoides and its morphological peculiarities have been sufficiently described and illustrated in an earlier publication to ensure success on the part of those who attempt to isolate it.